Valuing public goods more generally: The case of infrastructure - David Albouy; Arash Farahani (W.E. Upjohn Institute for Employment Research, 2017)
We examine the relationship between local public goods, prices, wages, and population in an equilibrium inter-city model. Non-traded production, federal taxes, and imperfect mobility all affect how public goods (or "amenities" more broadly) should be valued from data. Reinterpreting the estimated effects of public infrastructure on prices and wages in Haughwout (2002), we find infrastructure over twice as valuable with our more general model. New estimates based on more years, cities, and data-sets indicate stronger wage and positive population effects of infrastructure. These imply higher values of infrastructure to firms, and also to households if moving costs are substantial.
Keywords: H54; H2; H4; J3; R2; 330; Infrastructure; public goods; capitalization; valuation; nontraded goods; federal taxation; imperfect mobility